Pedagogy and the fairies - Glória Radino (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
Fairy tales always had an important pedagogic and therapeutic function. With the objective of educating and distracting, their stories continue alive and transmitting universal psychic phenomena. This article discusses the form by which fairy tales are used in an educational institution. Preoccupied in forming childhood scientifically, the school often disconsiders the child fantasy reducing the fairy tales to pedagogic support, levelling the child's universe.